PENGOLAHAN AIR MINUM SISTEM ADSORPSI MENGGUNAKAN ZEOLIT DAN KARBON AKTIF DI DONOTIRTO KRETEK KABUPATEN BANTUL - Yuliati, -; Suyanta, -; Aminatun, Tien (Universitas Negeri Yogyakarta, 2016)
The purpose of this activity is to (1) introduce the parameter of water hygene as physic, chemistry, and microbiology parameterto the community service participants. It was done through training and maintenence the drinking water processorfrom the well using adsorption system; and (2) increase the participants' knowledge about the correlation between clean water and water born diseases prevention. The public targetswere 35 audiencesfrom Donotirto citizen, community leader, and womens community. This methods used were programme socialization, lecture, discussion, training and maintenance, and evaluation. The findings are that the participants' knowledge about thehygene water parameters as physic, chemistry, and microbiology was increased. Drinking water treatment device had been produced and used. The quality of water in the well of Donotirto Kretek Bantul is better and qualified the quality standard tested by Health Department of Indonesia. Hence the society now consumes hygene and health water. The participants' knowledgeabout the correlation between the hygene water and water born diseases prevention was increased